RESPONSE OF FABA BEAN YIELD AND YIELD COMPONENTS TO DIFFERENT LEVELS OF NANO FERTILIZER - HUSSAIN, MOHAMAD ALI; MOSA, REZAN ESA; NOORI, MURADJAN M.M. (Journal of Duhok University, 2021)
Todays, the Nano fertilizers have become apioneer approach in farm of agriculture. A field experiment wasConducted at the farm Collage of Agricultural Engineering Science, University of Duhok, during the growing winter season 2019-2020 to investigate how Nano fertilizer affects the growth and yield of a local faba bean variety, the experiment units were arranged in a Randomize Complete Block Design with three replications. The result exhibited high significant effect of phosphorus and nitrogen and their interaction on all studied traits. The application ofphosphorus and nitrogen interactions increased plant height 153.4cm, first pod height 85.9cm, main brunches 3.6, number of pod plant-1, 38.3, seed pod-1 4.6,100 seed weight 189.4g and seed yield 294.5g at rate of108 P2O5 kg ha-1. We can conclude from this study that the application of proper amount of nitrogen and phosphorus increased the most growth traits and yield components. Furthermore, the findings revealed a substantial and positive correlation among seed yield and plant height. 0.96, first pod height 0.91, number of main brunches 0.56, number of pod plant-1 0.92, number of seed pod-1 0.90 and 100 seed weight 0.91. These results emphasize the role of these traits in selection of faba genotypes when putting in breeding program for improving faba bean production.